Hyperparasitoids (Hymenoptera: Encyrtidae and Signiphoridae) of Hypogeococcus spp. mealybugs (Hemiptera: Pseudococcidae) in Argentina and Paraguay - Serguei V. Triapitsyn; María B. Aguirre; Guillermo A. Logarzo; Stephen D. Hight (Acta Zoológica Lilloana, 2020)
Identified and reviewed taxonomically are the hyperparasitoids (Hymenoptera: Chalcidoidea) in Argentina and Paraguay associated with Hypogeococcus spp. (Hemiptera: Pseudococcidae), mealybugs that feed on various native cacti (Cactaceae) as well as some Amaranthaceae and Portulacaceae. The following genera and species were collected and reared in the course of surveys conducted in Argentina during 2010–2019 and in Paraguay during 2016–2019: Chartocerus argentinus (Brèthes) stat. rev. [reinstated as a valid species from the previous synonymy with Chartocerus niger (Ashmead)] and Chartocerus axillaris De Santis from Argentina (Signiphoridae), an undescribed Cheiloneurus sp. from Paraguay and Prochiloneurus argentinensis (De Santis) from Argentina (Encyrtidae). These are secondary parasitoids via Encyrtidae primary parasitoids of Hypogeococcus sp., candidate biological control agents against a Hypogeococcus sp. (commonly called the Harrisia cactus mealybug) that is devastating the native columnar cacti in Puerto Rico. The previously unknown male of Chartocerus argentinus is described, and a lectotype is designated for  Signiphora argentina Brèthes. Taxonomic notes are provided for Ablerus platensis (Brèthes) (Hymenoptera: Azotidae), for which a lectotype is designated (for Dimacrocerus platensis Brèthes); it is newly recorded from Paraguay. Hyperparasitoids can be detrimental to biological control programs, but their impact has often been unknown or underestimated. Taxonomic identification of the hyperparasitoids is the first step in assessing the potential negative impact to the natural control of Hypogeococcus spp. in South America.